INTEGRATING ARTIFICIAL INTELLIGENCE INTO LEARNING: ADVANTAGES AND CHALLENGES - Gulomov Shavkat Makhmudovich (Next Scientists Conferences, 2023)
The article examines the impact of modern artificial intelligence (AI) technologies on educational processes. The author analyzes the advantages provided by the integration of AI into the field of education, such as personalized learning, automation of assessment and the development of innovative educational programs. Special attention is paid to the challenges that may arise when integrating artificial intelligence into education. The author examines these challenges from the point of view of ethical issues, data privacy, and interaction between teachers and students. The article emphasizes the need for a balance between automation and human intervention in the educational process. Based on the analysis of current research and practical examples of the introduction of AI in education, the article offers recommendations for the effective integration of artificial intelligence technologies into curricula, taking into account the unique needs and context of educational institutions.